2017
DOI: 10.1158/1535-7163.mct-16-0390
|View full text |Cite
|
Sign up to set email alerts
|

Dual HDAC and PI3K Inhibitor CUDC-907 Downregulates MYC and Suppresses Growth of MYC-dependent Cancers

Abstract: Upregulation of MYC is a common driver event in human cancers, and some tumors depend on MYC to maintain transcriptional programs that promote cell growth and proliferation. Preclinical studies have suggested that individually targeting upstream regulators of MYC, such as histone deacetylases (HDAC) and phosphoinositide 3-kinases (PI3K), can reduce MYC protein levels and suppress the growth of MYCdriven cancers. Synergy between HDAC and PI3K inhibition in inducing cancer cell death has also been reported, but … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
104
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 117 publications
(108 citation statements)
references
References 46 publications
4
104
0
Order By: Relevance
“…As expected from our previous findings (Dominguez-Sola et al, 2012), Gene Set Enrichment Analysis (GSEA) (Subramanian et al, 2005) revealed strong upregulation of gene signatures associated with the cellular response to c-Myc (Schuhmacher et al, 2001; Sun et al, 2017; Zeller et al, 2003) (Fig. S1A).…”
Section: Resultssupporting
confidence: 86%
“…As expected from our previous findings (Dominguez-Sola et al, 2012), Gene Set Enrichment Analysis (GSEA) (Subramanian et al, 2005) revealed strong upregulation of gene signatures associated with the cellular response to c-Myc (Schuhmacher et al, 2001; Sun et al, 2017; Zeller et al, 2003) (Fig. S1A).…”
Section: Resultssupporting
confidence: 86%
“…Moving forward, as newer agents intended to target Myc family proteins are developed, our results suggest potential subgroups of particular interest for these approaches. Examples of potential strategies to target MYCN and downstream dependencies include bromodomain inhibition, dual HDAC/PI3K inhibition, MDM2 inhibition, and aurora A kinase inhibition . Whether patients with MYCN‐A as their sole unfavorable prognostic factor will be more likely to benefit from these strategies will require further study.…”
Section: Discussionmentioning
confidence: 99%
“…Currently, a phase I trial investigating a dual HDACi/PI3K inhibitor, CUDC‐907 is open to enrolling NC patients (NCT02307240). Activity of this drug in NC cells has been demonstrated in vitro and in vivo, and is associated with rapidly decreased MYC levels, a key oncogenic target of BRD4‐NUT . As with BETi, it is likely that effective therapy will require a combinatorial approach.…”
Section: Targeted Inhibitors Of Nut Carcinomamentioning
confidence: 99%